Effect of morphology of MWCNT on stability enhancement of nanofluids by using PVA surfactant - Rashidi, Saba; Abdullah, Luqman Chuah; Walvekar, Rashmi Gangasa; Khalid, Mohammad; Ahmadun, Fakhru'l-Razi; Md. Yasin, Faizah (2018)
Nanofluids are prepared by dispersing MWCNT into Polyvinyl Alcohol suspensions which distilled water used as base fluid. This paper summarizes the recent progress on the study of nanofluids which is investigates the effectiveness of Polyvinyl Alcohol (PVA) as surfactant for CNT/water nanofluids. The stability of nanofluids is measured by Zeta Sizer Nano-ZS (Malvern Instruments, ZEN3600). The zeta potential of the stable samples was analyzed. The morphological study of structure of CNT and its interaction with PVA dispersant was analyzed using SEM (FEI Quanta 400F, USA). The experimental results show that the zeta potential of stable samples indicated that the nanofluids are stable. The results demonstrated that zeta potential effect by concentration of CNT, it was increased with an increase in CNT concentration. The SEM results showed that the amount of PVA added to each CNT concentration is sufficient to provide maximum stability to the CNT-water nanofluids, no excessive agglomerations or significant clusters of PVA can be observed from the surface of CNT. In summary, this work provides useful insight on the behavior of CNT nanofluids.